7.2 THE MAIN REQUIREMENTS FOR THE DESIGNS OF A SEAMLESS TRACK - Makhamajanov Shukhratjon Shavkat ugli, Tadjibaev Sherzod Amirkulovich, Umaraliev Shahjahan Mukhammadrozi ugli, Abdualiev Elyorbek Begali ugli. (Innovative technologies in construction Scientific Journal, 2024)
The article presents the requirements for the structures and contents of the upper structure of the jointless track. The main structures used in world practice and rules for maintenance and repair of jointless tracks are described. Keywords: jointless track, rail lashes, track ejection, temperature stresses, equalizing spans. The basic requirements for the design, arrangement and condition of the upper structure of the jointless track are as follows [1.2.3.4.5.6.7.8.9.10]:• rails must have a sufficient margin of safety when working on bending and torsion to compensate for temperature stresses that can reach 125-150 MN/m;• the track grating must have sufficient rigidity to prevent transverse sliding of the track and disruption of its stability;• the ballast prism by design, material and condition must ensure a stable position of the track grating, sufficient resistance to longitudinal and transverse movements of sleepers, protect the track grating from theft and drain water;• intermediate and butt fasteners should ensure a change in the butt gap between adjacent lashes by no more than 0.010—0.011 m at maximum changes in rail temperature, as well as protect the lashes from theft along sleepers and the formation of a significant gap in the event of a through fracture of the rail lash.To date, two main designs of a temperature-stressed joint-free track are used in world practice:• a jointless track with intermediate fasteners, the elastic elements of which ensure a constant reliable connection of the rail lashes with a sub-rail base made of reinforced concrete frames or slabs, or reinforced concrete or wooden sleepers;• a jointless track on wooden sleepers with a crutch intermediate fastening, in which the connection of welded lashes with such sleepers is provided with the help of anti-theft devices.The jointless track is laid in straight sections of the track and curves with a radius of at least 350 m, and with a feasibility study approved by the head of the track service, in curves with radii of 300-350 m. For laying a jointless track, the roadbed must be strong and stable. Depths of more than 10 mm, subsidence, splashes and landslides of slopes are not allowed. The minimum width of the roadside for extracurricular lines and lines of grades 1-2 is 50 cm; 3rd - 45 cm, 4th—5th - 40 cm [2]. The ballast layer on sections of extracurricular lines and grades 1-4 should be crushed stone, on lines of grades 3-5, asbestos is allowed. Crushed stone should have fractions of 25-60 mm only of hard rocks with a strength of I20 and U75. Ballast prism in extracurricular areas, as well as on lines of 1-2 classes should have a shoulder width of 45 cm; 3-5 classes - 40 cm; slope steepness - 1:1.5. The thickness of the layer of crushed stone ballast under reinforced concrete sleepers — 40 cm, under the wooden ones — 35 cm. The maintenance of the jointless track is associated with special requirements in comparison with the link path, which is due to the presence of significant internal temperature forces appearing in the rail weaves with large differences in the actual temperature of the rails relative to the temperature at the time of laying them for permanent fastening.